Scientification of Norwegian football in the 1990s and the emergence of a new regime of knowledge - Hjelseth, A. (Soccer & Society, 2023)
The present paper aims to analyse the importance of science in Norwegian men`s football`s successful period in the 1990s. A main purpose is to examine how the ideas of Egil `Drillo` Olsen (coach of the men`s national team) and Nils Arne Eggen (Rosenborg BK) were part of a general trend of scientification of Norwegian elite sport at the time. By Norwegian standards, both the national team and Rosenborg achieved good results and made their mark internationally. We investigate how Drillo and Eggen not only improved sporting results, but also educated Norwegian football opinion. Their mission was mainly to optimize football performance based on scientific approaches in either football tactics isolated (Drillo) or in combination with more pedagogical and psychological theories of teamwork and interaction (Eggen). We discuss how their modern approach to science at that particular time and that particular stage of football`s development, and the regime of knowledge on which they built, created a competitive advantage to the rest of the world. After 2000, the rest of the world closed the gap, and the achievements of Norwegian football declined.